Credit vs. payment services: Financial development and economic activity revisited - Ricardo Bebczuk; Tamara Burdisso; Máximo Sangiácomo (Banco Central de la República Argentina (BCRA), Investigaciones Económicas (ie), 2012)
The purpose of this paper is to assess whether the banking system, over and beyond its credit function, has a significant impact on per capita GDP by providing means of payment. An annual database of 85 countries spanning the 1980-2008 period is exploited to this end. On the descriptive front, we find that richer economies exhibit higher and increasing levels of demand deposits and lower levels of currency than poor countries. While this was to be expected, more surprising is the fact that the currency to GDP ratio did not decrease much over time, regardless of income level differences. In turn, our regressions confidently support the hypothesis that banks contribute to economic development not only as credit suppliers but also by facilitating transactions. Specifically, along with the ratio of private credit to GDP, the ratio of demand deposits to currency seems to exert a positive influence on per capita GDP. The results are robust for different model specifications. These findings have valuable implications for a better understanding of the channels through which the banking system affects the economy.
Keywords: C33; G20; O40; 330; banking system; credit; growth; means of payment; Finanzsektor; Bank; Sozialprodukt; Welt